Supremacy of nanoparticles in the therapy of chronic myelogenous leukemia - Gopalarethinam Janani; Agnishwar Girigoswami; Koyeli Girigoswami (International Association of Physical Chemists (IAPC), 2023)
Background and purpose: The reciprocal translocation of the ABL gene from chromosome 9 to chromosome 22 near the BCR gene gives rise to chronic myelogenous leukemia (CML). The translocation results in forming the Philadelphia chromosome (BCR-ABL) tyrosine kinase. CML results in an increase in the number of white blood cells and alteration in tyrosine kinase expression. CML prognosis includes three stages, namely chronic, accelerated, and blast. The diagnosis method involves a CT scan, biopsy, and complete blood count. However, due to certain disadvantages, early diagnosis of CML is not possible by traditional methods. Nanotechnology offers many advantages in diagnosing and treating cancer. Experimental approach: We searched PubMed, Scopus and Google Scholar using the keywords Philadelphia chromosome, bionanotechnology, tyrosine kinase pathway, half-life, passive targeting, and organic and inorganic nanoparticles. The relevant papers and the classical papers in this field were selected to write about in this review. Key results: The sensitivity and specificity of an assay can be improved by nanoparticles. Utilizing this property, peptides, antibodies, aptamers, etc., in the form of nanoparticles, can be used to detect cancer at a much earlier stage. The half-life of the drug is also increased by nanoformulation. The nanoparticle-coated drugs can easily escape from the immune system. Conclusion: Depending on their type, nanoparticles can be categorized into organic, inorganic and hybrid. Each type has its advantages. Organic nanoparticles have good biocompatibility, inorganic nanoparticles increase the half-life of the drugs. In this review, we highlight the nanoparticles involved in treating CML.